Utilizing Know, Want, Learn (KWL) Strategy in Teaching Reading Comprehension of Narrative Text - Rayhan Krismansyah; Mobit; Indah Purnama Dewi (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
Reading is an ability that everyone must have, reading is also a bridge to new knowledge. In fact, students often struggle with reading such as identifying texts, finding the main topic, extracting information, grasping the overall meaning, and connecting text events to real life. This study aims to explore the implementation of the KWL (Know, Want, Learn) strategy in teaching reading comprehension of narrative texts and student perception in learning reading narrative text at junior high schools in Karawang. The KWL strategy is used to help students understand narrative texts more deeply, with stages that include identifying prior knowledge, learning objectives, and reflecting on the understanding gained. This study uses a qualitative approach with a case study method to analysed the data found. The participants used in this research amounted to 8 students. besides that, the data collection technique uses 3 ways, namely observation, interview, and documentation. The findings show that the KWL strategy is helping in students organize information and improve their understanding of the text, some students also said that this strategy really helped students and understand the material. However, challenges such as low student interest in reading and limited learning media are obstacles in the implementation process. However, students' perceptions of the KWL strategy are positive, where students feel more actively involved in the learning process and are more motivated to read narrative texts. Therefore, the results show that KWL strategy helps students organize information and improve their understanding of the text. Although this strategy is effective, there are challenges such as students' low reading interest and limited learning media. However, students' perception of KWL strategy remains positive, and helping where they feel more engaged and motivated in the learning process.